A unified viscoplastic model for high temperature low cycle fatigue of service-aged P91 steel - Barrett, R.A.; Farragher, T.P.; Hyde, Christopher J.; O'Dowd, N.P.; O'Donoghue, P.E.; Leen, S.B. (American Society of Mechanical Engineers, 2014)
The finite element (FE) implementation of a hyperbolic sine unified cyclic viscoplasticity model is presented. The hyperbolic sine flow rule facilitates the identification of strain-rate independent material parameters for high temperature applications. This is important for the thermo-mechanical fatigue of power plants where a significant stress range is experienced during operational cycles and at stress concentration features, such as welds and branched connections. The material model is successfully applied to the characterisation of the high temperature low cycle fatigue behavior of a service-aged P91 material, including isotropic (cyclic) softening and nonlinear kinematic hardening effects, across a range of temperatures and strain-rates.